WILL NOVEL EDUCATION POLICY STIMULATE BUSINESS MANAGEMENT OPPORTUNITIES IN BANGLADESH: A CRITICAL ANALYSIS AND LESSONS TO BE LEARNED FROM THE UNITED STATES - Mohaimenul Islam Jowarder (Universitas Nusa Cendana, 2023)
The purpose of this study is to understand how the novel education policy, which is to be implemented in 2025 in Bangladesh, will foster business management opportunities and the probable lessons from the United States. This study conducted a mixed methodology analysis followed by a purposive sampling method. 200 students from primary to higher secondary levels and 20 teachers were selected. We also conducted Four Focus Group Discussions with curriculum experts who were directly involved with developing this method in Bangladesh. An exclusive interview with the President of Hyundai Motors Asia assisted in exploring the context in-depth. The study revealed a positive response from students, ranging from prospective career opportunities to rising interests to implement their acquired knowledge, eradicating the fear of science as well as emphasizing becoming small business entrepreneurs and believing in stimulating business opportunities. Further research is encouraged to assess the impacts of this educational reform in diverse employment sectors in-depth. Keywords: Education Policy; Business Management; Bangladesh; United States